An Islamic Law Review of Conditional Debt Practices Between Collectors and Fishermen - Kamisatun; Nilfatri; Hasna Dewi; Kurniawan; Zeni Sunarti; Reza Okva Marwendi (Zabags Qu Publish, 2025)
This study examines conditional debt practices between collectors (fish buyers) and fishermen in Tanjung Solok Village, Kuala Jambi Subdistrict, a traditional economic relationship rooted in urgent livelihood needs yet prone to contractual inequities from an Islamic law perspective. The primary objective is to analyze how these conditional lending arrangements are executed and to assess their validity under Islamic legal principles. Employing a qualitative socio-legal (legal empiricism) approach, the research integrates field data collected through interviews, direct observation, and documentary review with normative analysis grounded in muamalah theory and contemporary contract principles in Islamic finance. Findings reveal that transactions are predominantly oral, lack written agreements or formal witnesses, and commonly impose a requirement to resell catches to the collectors at prices below prevailing market rates, producing a structural imbalance in bargaining power. Normative analysis indicates that such practices conflict with the Islamic tenets of contractual clarity, distributive justice, and the prohibition of exploitative gains. The study contributes empirically and conceptually to Islamic legal scholarship by bridging muamalah theory and ground-level practice, and it offers a foundation for community-level syariah-compliant interventions and policy measures to protect economically vulnerable fisher cohorts.